KUALITAS PELAYANAN PENETAPAN PENSIUN OTOMATIS BERBASIS LESS PAPER BAGI PEGAWAI NEGERI SIPIL DI LINGKUNGAN PEMERINTAH PROVINSI SULAWESI UTARA - Erni Hidayanti (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
The purpose of this study was directed to examine the quality of service for determining less paper-based automatic pensions for Civil Servants in the North Sulawesi Provincial Government. This research is descriptive qualitative with data collection techniques in the form of interviews, observations and documentation. Implementation of the determination of less paper-based automatic pensions for Civil Servants in the North Sulawesi Provincial Government has not gone well, due to the absence of Standard Operating Procedures (SOP) for determining less paper-based automatic pensions, lack of transparency, weak socialization, weak data reconciliation, lack of human resources. The apparatus, there is no innovation in the development of less paper-based pension processing, the condition of civil servants who will enter the retirement age limit has not responded to the implementation of the less paper-based automatic pension determination. Therefore, it takes a strong commitment and desire from the North Sulawesi Provincial Government, especially the Regional Personnel Board of North Sulawesi Province in making innovations in developing less paper-based automatic pension determinations to create automatic pension service flows that meet service quality standards, making it easier for pension recipients to receive pension decisions.